2014
DOI: 10.1111/ipd.12149
|View full text |Cite
|
Sign up to set email alerts
|

The dental health of children subject to a child protection plan

Abstract: Children subject to child protection plans had significantly higher levels of dental caries in the primary dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 4 publications
3
30
1
2
Order By: Relevance
“…[7][8][9][10] Child maltreatment is associated with poor selfperceived oral health, and maltreated children have a higher incidence of untreated tooth decay, poorer oral hygiene, worse oral health and more missed health care appointments than the general population. [11][12][13][14][15][16][17] Further, failure to meet the basic dental needs of a child can result in ache, inhibit normal development and reduce the child's quality of life, and is considered as dental neglect. [1,18] To prevent child maltreatment and limit its consequences, it is crucial to identify maltreated children as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Child maltreatment is associated with poor selfperceived oral health, and maltreated children have a higher incidence of untreated tooth decay, poorer oral hygiene, worse oral health and more missed health care appointments than the general population. [11][12][13][14][15][16][17] Further, failure to meet the basic dental needs of a child can result in ache, inhibit normal development and reduce the child's quality of life, and is considered as dental neglect. [1,18] To prevent child maltreatment and limit its consequences, it is crucial to identify maltreated children as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Among child victims of abuse in UK, a statistically significant difference with respect to dental caries in the primary dentition occurred compared with the control children, but for the permanent dentition there was no statistically significant difference between the two groups [15].…”
Section: Literature Review and Discussionmentioning
confidence: 80%
“…Some authors have suggested that the lack of motivation and interest of parents in maintaining oral health of children victims of abuse and low self-esteem of them, can take them to have high prevalence of caries and also less untreated teeth [13,15,25,28,30], in addition to high levels of gingivitis [18] when compared to children with no history of violence.…”
Section: Introductionmentioning
confidence: 99%
“…Considering oral health problems, exposure to childhood violence may also result in worse oral health conditions years later. Scientific evidence has shown that physically abused children are more likely to experience increased incidence of dental caries, more missing teeth, more filled teeth, and higher occurrence of anterior open bite . In addition, they frequently present oral and maxillofacial traumas associated with physical aggression and may have significant impacts on oral health‐related quality of life (HRQoL), following a multidimensional perspective (organic, functional, and aesthetic), being usually associated with high morbidity rates …”
Section: Introductionmentioning
confidence: 99%